Mixed methods research in b-learning modality: asynchronous communication analysis - López Gómez, Ernesto; Camilli Trujillo, Celia (Historia y Comunicación Social, 2014)
The aim is to analyze the asynchronous communication in b-learning mode between teachers and students through mixed methods research. Consultations have been categorized through content analysis to forums, emails and focus group and from these results, a Likert scale has developed. The findings show the contrast between the actual speech and perception of students as well as difficulties associated with the use of technology, the importance of planning the learning and the need for continuous assessment supported by mentoring.
Keywords: Blended learning; mixed methods research; asynchronous communication; interpersonal communication; tutoring; EHEA.